Consolidation in dialysis Markets—Causes, consequences, and the role of policy. Issue 1 (12th January 2020) - Saeed, Maryam K.; Ho, Vivian; Erickson, Kevin F.
Abstract: The dialysis industry is one of the most highly concentrated healthcare sectors in the United States. Despite decades of growth in the number of patients with end‐stage renal disease and in the size of dialysis markets, two large dialysis organizations currently care for more than two‐thirds of the dialysis population. Economies of scale, bargaining leverage with suppliers and private insurers, barriers to entry, and government regulations have contributed to highly concentrated dialysis markets by conferring advantages to larger organizations. Consolidated dialysis markets have coincided with both positive and negative trends in healthcare costs and outcomes. Costs per patient receiving dialysis have grown at a slower rate than per capita Medicare costs, while access to dialysis care remains available across a wide socioeconomic range. Mortality rates have declined despite a sicker dialysis patient population. Yet, concerns remain about the cost and quality of dialysis care. Evidence suggests that chain ownership, for profit status, and less market competition may negatively impact health outcomes. Future policies and innovations involving kidney health may temporarily disrupt consolidation. However, if the underlying mechanisms that contributed to past consolidation persist, dialysis markets may remain highly concentrated over the long term.